(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study was carried out to investigate the parental and teacher’s involvement as correlate of special-need pupils’ achievement and interest in mathematics. The researchers adopted a correlation research design and the area of study was the special-needs schools. Four (4) special schools were selected through purposive sampling technique. The instruments used for data collection were: (i) parental involvement scale (PIS), (ii) Teachers involvement scale (TIS) and (iii) Special-needs pupils interest scale (SPIS). Each of the instruments was structured on a four-point rating scale by the researcher. The research instruments were face-validated by two experts in science education and one expert in special education. Cronbach Alpha technique was used to ascertain the internal consistency of the instruments and reliability indices of 0.96, 0.96 and 0.93 were obtained for PIS, TIS and SPIS respectively. The data collected was analyzed using the regression analysis and analysis of variance regression analysis was used to test the hypothesis at 0.05 level of significance. The finding of the study showed among others that parents, teachers and interest of the special-needs pupils have positive significance in the achievement of the pupils in mathematics. Based on the findings and implications of the study, recommendations were made.